1997
DOI: 10.1002/j.1550-8528.1997.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Attitudes and Behaviors Related to Nutrition, Body Size, Dieting, and Hunger in Russian, Black‐American, and White‐American Adolescents

Abstract: were no significant differences among white-American girls and Russian girls, and there were no ethnic differences between boys in the prevalence of dieting. WhiteAmerican girls and black-American girls were much more likely to identify being overweight as an important nutritional concern than were Russian girls (odds ratios >lo), and there were no ethnic differences among boys. We conclude that preferences for body size, the prevalence of dieting, and concerns about being overweight were similar in Russian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Our findings did show that AA adolescents preferred a larger ideal body size than CC adolescents. This is consistent with previous research showing that AA girls prefer a larger body weight than CC girls (51). HA adolescents were somewhat in the middle, not showing a significant difference in ideal body size from either CC or AA groups, a finding that was similar to that reported by Story et al (52).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings did show that AA adolescents preferred a larger ideal body size than CC adolescents. This is consistent with previous research showing that AA girls prefer a larger body weight than CC girls (51). HA adolescents were somewhat in the middle, not showing a significant difference in ideal body size from either CC or AA groups, a finding that was similar to that reported by Story et al (52).…”
Section: Discussionsupporting
confidence: 93%
“…[19][20][21] Furthermore, groups as dissimilar as African Americans, American Indians, Alaskan natives and Russians express greater body satisfaction than whites. 8,22 Thus studies regarding how these groups determine their appropriate body weight might also discover more of a focus on being healthy versus appearance. Finally, many successful health promotion efforts involve community members, which implies the importance of peers in education.…”
Section: Discussionmentioning
confidence: 99%
“…53 Female adolescents may be more likely to care about their body image, 53 and some studies show that body dissatisfaction is more prevalent among girls. [54][55][56] A recent comparative study of eating disorders showed that a substantial proportion of female high school students in Hong Kong (74%), Shenzhen (61%), and rural area of Hunan (44.3%) desired a lower BMI. 57 In the present study, boys with high BMI experienced less depressive symptoms than did girls with high BMI.…”
Section: Discussionmentioning
confidence: 99%